Gastrointestinal Parasites Affecting Non-Human Primates That Are Kept Ex Situ and Their Handlers in Different Brazilian Institutions: Diagnosis and Analysis of Risk Factors - Dib, Laís Verdan; Barbosa, Alynne; da Silva, Breno; Pissinatti, Alcides; Moreira, Silvia; Tavares, Maria Clotilde; Teixeira, Rodrigo [UNESP]; da Costa, André Luíz; Muniz, José Augusto; Junglos, Amauri; Hirano, Zelinda Maria; Amendoeira, Maria Regina (MDPI, 2023)
Aim: Determining gastrointestinal parasites’ frequency in non-human primates (NHPs) and handlers in different Brazilian institutions, and associate it with management information. Methods: Different institutions in São Paulo (A), Brasília (B), Rio de Janeiro (C), Pará (D) and Santa Catarina (E) were included in the study. Fecal samples were processed by using coproparasitological techniques; information about NHP handling and professionals’ routine were collected through the use of questionnaires. Results: In total, 33.1% of 511 NHP samples were positive for parasites; the Entamoebidae Group and Strongyloides sp.-compatible eggs were the most detected protozoa and helminths, respectively. The Entamoebidae Group was mainly diagnosed in Alouatta from Institutions E and D, and was also the only parasite detected in handlers. Strongyloides-compatible eggs were mostly evident in fecal samples collected from Cebidae from Institutions B and D. Some risk factors associated with parasite infection were a high number of animals in the same enclosure and their use for research protocol purposes, whereas quarantine, a post-infection vacant period in enclosures and antiparasitic supply were categorized as protective factors against these agents’ infection. Conclusions: Parasites showing different transmission routes but concomitantly circulating in NHP institutions located in different Brazilian regions were identified in the current study, with an emphasis on those presenting zoonotic potential.
Keywords: helminths; non-human primates; protozoa; risk factors; zoonosis